2021
DOI: 10.1007/s00277-021-04471-6
|View full text |Cite
|
Sign up to set email alerts
|

Glasdegib in combination with low-dose Cytarabine for the outpatient treatment of relapsed or refractory acute myeloid leukemia in unfit patients

Abstract: We retrospectively collected clinical data on 31 relapsed or refractory acute myeloid leukemia (R/R AML) patients who were treated with outpatient glasdegib and low-dose Cytarabine (LDAraC) at our institution. The median age was 67 years (45–86). The median Eastern Cooperative Oncology Group performance status was 2 (1–3). The patients had previously received a median number of 2 (1–4) treatment lines, 61% (19/31) had been treated with intensive chemotherapy, 29% (9/31) had relapsed after allogeneic stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although no direct comparison was performed, due to the similarity of the populations evaluated in the VIALE‐A and VIALE‐C trials and with better results shown with venetoclax combination, glasdegib is not widely used in patients with ND AML deemed unfit for intensive chemotherapy. The efficacy of glasdegib with LDAC in the R/R setting was evaluated in a small retrospective study that demonstrated composite CR (CR + CRp) rates of 21% with a median OS of 3.9 months 154 . Thus, the role of glasdegib in the treatment algorithm for newly diagnosed older adult setting is not yet determined, as other alternatives seem more appealing.…”
Section: Updates In Treatments and Combination Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no direct comparison was performed, due to the similarity of the populations evaluated in the VIALE‐A and VIALE‐C trials and with better results shown with venetoclax combination, glasdegib is not widely used in patients with ND AML deemed unfit for intensive chemotherapy. The efficacy of glasdegib with LDAC in the R/R setting was evaluated in a small retrospective study that demonstrated composite CR (CR + CRp) rates of 21% with a median OS of 3.9 months 154 . Thus, the role of glasdegib in the treatment algorithm for newly diagnosed older adult setting is not yet determined, as other alternatives seem more appealing.…”
Section: Updates In Treatments and Combination Therapiesmentioning
confidence: 99%
“…The efficacy of glasdegib with LDAC in the R/R setting was evaluated in a small retrospective study that demonstrated composite CR (CR + CRp) rates of 21% with a median OS of 3.9 months. 154 Thus, the role of glasdegib in the treatment algorithm for newly diagnosed older adult setting is not yet determined, as other alternatives seem more appealing.…”
Section: Glasdegibmentioning
confidence: 99%
“…Zucenka et al have reported the use of glasdegib combined with low-dose cytarabine in 31 patients affected by R/R AML, 9 (29%) of whom relapsing early after HSCT. The median overall survival was 10.4 months and interestingly, an univariate analysis revealed that previous HSCT and venetoclax exposure did not significantly influence the survival [ 185 ].…”
Section: Novel Targeted Agents In Developmentmentioning
confidence: 99%
“…Glasdegib was tested in combination with low dose cytarabine in the frontline treatment of AML in patients who are ineligibile for intensive chemotherapy (53). It was used in the R/R setting with modest efficacy (54). Other novel agents include MCL1 inhibitors, MDM2 inhibitors especially in combination with venetoclax (55,56).…”
Section: Innovative Therapiesmentioning
confidence: 99%